Basipetal auxin versus acropetal cytokinin transport, and their interaction with NO3 fertilisation in cotyledon senescence and sink:source relationships in cucumber (Cucumis sativus L.). (22nd July 2015) - Bangerth, K.‐F.; Adams, W.
Abstract The paramount role of cytokinins (CKs) in initiation, as well as prevention, of senescence is well established. In recent years, experimental methods have become available to raise and lower the CK concentration and experimentally manipulate senescence. Decapitating the apical shoot and adding the synthetic auxin naphthylacetic acid to the cut stem reduced endogenous CKs to low levels. Conversely, if no auxin was applied, xylem and leaf CK levels increased dramatically, indicating that basipolar auxin transport is a key determinant in the synthesis of CKs and is potentially more important than NO3. Manipulating the concentration of applied NO3 caused considerable variation in leaf CK levels and concomitant changes in senescence. These and other results suggest that the frequently discussed decrease in nitrogen use efficiency (NUE) may be more highly regulated by CKs than by NO3. Analysis of the re‐metabolisation and re‐allocation of chlorophyll, proteins, amino acids and starch in three different cucumber cultivars indirectly showed that these metabolites were significantly affected by the concentration of CKs in the leaves. Further research in this area may allow leaf senescence and plant yield to be more efficiently regulated by manipulating CKs and/or basipolar auxin transport instead of nitrate.